Inventarisasi Jenis dan Resep Kue Tradisional sebagai Oleh-Oleh di Kecamatan Batang Kapas - Annisa Rahmasari; Elida (Indo Publishing, 2025)
This study aims to compile a detailed inventory of the types and recipes of traditional Balinese cakes in Batang Kapas District. This includes: 1) describing the types of traditional cakes sold as souvenirs in Batang Kapas District. 2) recording and describing traditional cake recipes sold as souvenirs in Batang Kapas District, including the names of the dishes, ingredients, tools, and processing methods. This study employed qualitative descriptive methods. The research location was the main traditional market in Batang Kapas District. The informants were elderly women and vendors knowledgeable about the types and recipes of traditional cakes. The study found 13 wet cake recipes and 10 dry cake recipes. These cakes are made from rice flour, glutinous rice flour, glutinous rice, sago flour, cassava, sweet potatoes, and peanuts. Furthermore, these traditional cakes often use coconut, either coconut milk or grated coconut. Traditional cake processing techniques include steaming, boiling, frying, baking, and roasting.